A Nonsense N -Terminus NFKB2 Mutation Leading to Haploinsufficiency in a Patient with a Predominantly Antibody Deficiency (2020)
ABSTRACT: The noncanonical NF-κB pathway is implicated in diverse biological and immunological processes. Monoallelic C-terminus loss-of-function and gain-of-function mutations of NFKB2 have been recently identified as a cause of immunodeficiency manifesting with common variable immunodeficiency (CVID) or combined immunodeficiency (CID) phenotypes. Herein we report a family carrying a heterozygous nonsense mutation in NFKB2 (c.809G > A, p.W270*). This variant is associated with increased mRNA decay and no mutant NFKB2 protein expression, leading to NFKB2 haploinsufficiency. Our findings demonstrate that bona fide NFKB2 haploinsufficiency, likely caused by mutant mRNA decay and protein instability leading to the transcription and expression of only the wild-type allele, is associated with clinical immunodeficiency, although with incomplete clinical penetrance. Abnormal B cell development, hypogammaglobulinemia, poor antibody response, and abnormal noncanonical (but normal canonical) NF-κB pathway signaling are the immunologic hallmarks of this disease. This adds a third allelic variant to the pathophysiology of NFKB2-mediated immunodeficiency disorders.